Desain Majalah Guna Menunjang Media Informasi Pada SMK Al-Ijtihad Tangerang - Dede Cahyadi; Aris Aris; Dennis Laloan (UNIVERSITAS RAHARJA, 2020)
Basically, the development and progress of information technology is increasingly rapid. At present information can be obtained from anywhere, and one of them through print media such as magazines and brochures. Information plays a very important role in people's lives today, with information making it easier for people to find the information they want to find. Especially print media in the form of design, and one of the design media that can later be used as information and promotional media is magazines and brochures. Therefore, the authors make the media design of magazines and brochures at the AL-Ijtihad Tangerang Vocational School so that they can be used to provide information and also promotions that are easily known by the public, and the promotion becomes more effective and attractive with the design of the magazine and brochure. For later it is hoped that it can improve the image of the school and can be promoted to students who wish to continue their education to a vocational level. The design of the magazine and brochure design itself was created using Adobe Photoshop cs6 design software, therefore the authors did the design of the magazine and brochure design media summarized in this thesis report. And hopefully the school can be implemented as a medium of information and promotion to attract prospective new students.